Ethanol extract of Sargarsum fusiforme alleviates HFD/STZ-induced hyperglycemia in association with modulation of gut microbiota and intestinal metabolites in type 2 diabetic mice. (September 2021) - Wu, Siya; Zuo, Jihui; Cheng, Yang; Zhang, Ya; Zhang, Zhongshan; Wu, Mingjiang; Yang, Yue; Tong, Haibin
Graphical abstract: Highlights: Ethanol extract (EE) of S. fusiforme alleviated HFD/STZ-induced T2DM. EE modulated the structure and composition of gut microbiota in T2DM mice. EE reduced levels of intestinal metabolites BCAA and AAA and increased 4-HPA in T2DM mice. Abstract: Type 2 diabetes mellitus (T2DM) is considered a rapidly growing chronic disease that threatens human health worldwide. Extracts of various seaweeds have been shown to have anti-diabetic activity. Sargarsum fusiforme, an edible brown seaweed, has been shown to possess anti-inflammatory, anti-diabetic and anti-obesity activities. In this study, we investigated the beneficial effect of an ethanol extract of S. fusiforme (EE) on type 2 diabetes in mice induced with high-fat diet (HFD) and streptozotocin (STZ). Administering EE to the diabetic mice significantly reduced food intake, water intake and fasting blood glucose (FBG), while improving glucose tolerance, lipid profile and ameliorating hepatic oxidative stress. Furthermore, these animals also exhibited significantly diminished epididymal fat deposition, as well as less pathological changes in the heart and liver tissues, while displaying some highly enriched benign gut bacteria (e.g., Intestinimonas, Oscillibacter, Lachnoclostridium, unidentified_Lachnospiraceae, Roseburia and Anaerotruncus ) and a lower abundance of bacteria associated with diabetes or other metabolic diseases (e.g., Enterorhabdus and Romboutsia ). Metabolomic analysis revealed reduced levels of branched-chain amino acids (BCAA), such as l -valine and l -isoleucine, aromatic amino acids (AAA), such as l -tyrosine and l -phenylalanine, and increased levels of 4-hydroxyphenylacetic acid (4-HPA) in the gut content, suggesting that EE may impact T2DM through modulation of these compounds in the gut of the animals. Taken together, the results implied that S. fusiforme may contain valuable active components other than polysaccharides that have potential benefit in alleviating T2DM.